Effects of low- and high-calcium fly ash on the water resistance of magnesium oxysulfate cement. (10th January 2020) - Zhang, Na; Yu, Hongfa; Gong, Wei; Liu, Ting; Wang, Nan; Tan, Yongshan; Wu, Chengyou
Highlights: The properties of MOSC with L-FA or H-FA during water immersion are studied. The compressive strength of MOSC decreases first and then increases after immersion. Restricting the expansion contributes to the densification of the microstructures of MOSC. A small number of 5·1·7 phases can form after immersion in water. Abstract: To expand the application range of magnesium oxysulfate cement (MOSC) and the utilization of fly ash, the water resistance of MOSC mixed with low-calcium fly ash (L-FA) or high-calcium fly ash (H-FA) was studied. The softening coefficients and volume stability were tested to evaluate the water resistance of MOSC. The hydration products and microstructures of MOSC prepared without L-FA or H-FA (denoted as C) and MOSC prepared with L-FA (L-FM) or H-FA (H-FM) were characterized by quantitative X-ray diffraction (QXRD), mercury intrusion porosimetry (MIP), thermogravimetry (TG), and scanning electron microscopy (SEM). The results show that the expansion stress and the volume deformation caused by the transformation of residual MgO into Mg(OH)2 are the main reasons for the decrease in the compressive strength of MOSC after its immersion in water. The formation of few 5·1·7 whiskers and the restraints on the expansion increase the compactness of the MOSC, which makes the compressive strengths and softening coefficients of C, L-FM and H-FM increase gradually with an increase in the immersion time. The softening coefficients of C, L-FM and H-FM immersed in water for 90 days are 0.97, 1.00 and 0.84, respectively. Although the softening coefficient of H-FM is not as good as that of C and L-FM due to the formation of CaSO4 ·2H2 O, the compressive strength and the compactness of H-FM immersed in water for 90 days are still higher than those of L-FM, which indicates that H-FA has good application prospects in MOSC.